Promosi Menggunakan Desain Kemasan untuk Meningkatkan Minat Beli dengan Aplikasi Corel Draw X-7 pada Pitaburger Wings Malang - Ario Bimo Fatahillah; Dwi Sudjanarti (INDO PUBLISHING, 2025)
The rapid growth of the culinary industry encourages businesses to innovate, particularly through packaging design as a promotional medium. Pitaburger Wings Malang has been using simple packaging that lacks sufficient information, making it less effective in increasing consumer purchase intention. This study aims to analyze and redesign the packaging using CorelDRAW X-7 to create a more communicative and attractive design. The research applied an action research method conducted in two cycles, with data collected through observation, interviews, questionnaires, and documentation from 10 respondents consisting of the business owner, design experts, a marketing expert, and consumers. The effectiveness of the design was evaluated using the VIEW (Visibility, Information, Emotional Appeal, Workability) and AIDA (Attention, Interest, Desire, Action) models. Findings in Cycle I indicated weaknesses in information readability, requiring improvements. After revisions in Cycle II, all VIEW and AIDA indicators showed improvement, indicating that the new packaging design is more visually appealing, clearer in conveying information, functional, and effective in attracting consumer attention and purchase intention. Therefore, the redesigned packaging is considered feasible for use as a promotional medium and has the potential to enhance the competitiveness of Pitaburger Wings Malang products.